2013
DOI: 10.1682/jrrd.2012.05.0100
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity of Comprehensive High-Level Activity Mobility Predictor (CHAMP) for male servicemembers with traumatic lower-limb loss

Abstract: Abstract-This study examined the convergent construct validity of a new performance-based assessment instrument called the Comprehensive High-Level Activity Mobility Predictor (CHAMP) as a measure of high-level mobility in servicemembers (SMs) with traumatic lower-limb loss (LLL). The study was completed by 118 SMs. Convergent construct validity of the CHAMP was established using the 6-minute walk test (6MWT) as a measure of overall mobility and physical function and the Amputee Mobility Predictor (AMP) as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 29 publications
0
46
2
Order By: Relevance
“…The mean Amputee Mobility Predictor with Prosthesis scores demonstrate that both unilateral and multiple amputees achieved mobility comparable with that of active adults and community ambulators with lower limb loss, respectively. 7 A recent study 16 of US service members with lower limb loss who had completed rehabilitation reported comparable findings (mean Amputee Mobility Predictor with Prosthesis scores between 41 and 46 in unilateral amputee and bilateral amputee groups). This is important because it demonstrates, for the first time, the similarities in functional mobility achieved between US and UK military personnel injured during the Iraq and Afghanistan conflicts.…”
Section: Discussionmentioning
confidence: 88%
“…The mean Amputee Mobility Predictor with Prosthesis scores demonstrate that both unilateral and multiple amputees achieved mobility comparable with that of active adults and community ambulators with lower limb loss, respectively. 7 A recent study 16 of US service members with lower limb loss who had completed rehabilitation reported comparable findings (mean Amputee Mobility Predictor with Prosthesis scores between 41 and 46 in unilateral amputee and bilateral amputee groups). This is important because it demonstrates, for the first time, the similarities in functional mobility achieved between US and UK military personnel injured during the Iraq and Afghanistan conflicts.…”
Section: Discussionmentioning
confidence: 88%
“…There are several examples in which servicemembers who participated in intensive rehabilitation programs and had access to regular prosthetic care demonstrated smaller deficits than previously reported. For example, they have performed similarly to their nondisabled counterparts in areas such as activity performance, gait biomechanics, and walking stability [34][35][36][37][38][39][40][41]. It is important to recognize that the similarities observed here and elsewhere, while encouraging, do not represent an absence of dysfunction or the full restoration of function in all people or across all aspects of life.…”
Section: Russell Esposito Et Al Metabolic Demand Of Walking In Amputeesmentioning
confidence: 83%
“…Impairment variables of THES, SLB, hip extension, RoM restriction, and waist circumference comprised modifiable variables that can be directly influenced by rehabilitation intervention. Nonmodifiable personal factors of age and number of comorbidities were included in the regression analyses, since both variables have been associated with a decline in mobility in people with LLA …”
Section: Discussionmentioning
confidence: 99%